Multiple levels of control determine how E4bp4/Nfil3 regulates NK cell development - Kostrzewski, Tomasz (J Immunol, 2018)
The transcription factor E4bp4/Nfil3 has been shown to have a critical role in the development of all innate lymphoid cell types including Natural Killer (NK) cells. Here, we show that post-translational modifications (PTMs) of E4bp4 by either SUMOylation or phosphorylation have profound effects on both E4bp4 function and NK cell development. We examined the activity of E4bp4 mutants lacking PTMs and found that Notch1 was a novel E4bp4 target gene. We observed that abrogation of Notch signalling impeded NK cell production and the total lack of NK cell development from E4bp4(-/-) progenitors was completely rescued by short exposure to Notch peptide ligands. This work reveals both novel mechanisms in NK cell development by a transcriptional network including E4bp4 with Notch and that E4bp4 is a central hub to process extrinsic stimuli.